Experimentation in Postmodern art Arte Povera" as an example (Damascus University Journal for engineering sciences, 2021)
There is no separation between modernity and experimentation, formation and renewal, which leads to change the structure and function of the artwork, by creating new tools and vocabulary that revive the artwork and make it different. for experimentation to become the tool and bearer of the artwork, for paralleling the scientific and the aesthetic. Several contemporary experiments have used technique to present perceptions that create a dialogue with prevailing ideas, and engage with the recipient and activate his presence to become part of the artwork and not just a viewer.This research can be categorized under "art techniques" and it aims to highlight the importance of the phenomenon of experimentation, for innovation in postmodern arts in the second half of the twentieth century, and to keep pace with the philosophy and culture of society in its vocabulary and new modernist techniques.It is a descriptive-analytical research. depicts the situation of postmodernity, and its intellectual justifications, and social, economic motivations, in terms of innovation and its tendencies.this research presents "Arte Povera" as an example  for contemporary artistic practices, by monitoring the structural and aesthetic method, and examining its dimensions and indication. After which, new concepts and technologies have been proposed to link art with social, political and cultural realities that these artists live, and allow them to freely express the issues of their societies
Keywords: Experimentation; Postmodern art; Arte Povera